Bilingual Khmer/English Literature: Contestation Practices and Strategies in the Cambodian Literary Field - Fransiskus Tri Wahyu Setiawan (Center for Southeast Asian Social Studies (CESASS), 2018)
The study aims to examine how different agents namely individuals, groups, and organizations form the Cambodian literary field compete through selected practices. Certain strategies are applied in accordance to the rules of game in the literary field production. Having different habitus and capitals, agents struggle and compete for positions in the literary field. Applying literary study and classical ethnographic methods this study shows that political distance from the government in the field of cultural production allows external forces to interfere and reshape the Cambodian literary field. Agents make the structure and are structured in dynamic competition within the field. Strategies are mainly intended to create new network and to gain legitimacy, thereby accumulating capitals. Bilingual Khmer/English literature is important literary phenomenon in Cambodia as it indicates practices of contestation in response to the global field of cultural production.